The Guangzhou Modern Opera Performance Book - Li, Yang; Sartjinpong , Nayos; Yodwised, Chutasiri (Journal of Roi Kaensarn Academi, 2024)
From problems that have accumulated for a long time, experts have given advice and solutions by writing a performance book on opera vocal techniques, paralleling music score and theory, providing a broad concept, and targeted sound skill training. The research article aims to study Guangzhou Modern opera and to write Guangzhou Modern opera performance book. The researcher used quantitative research methods to gather data from three experienced key informants, constructing the Guangzhou modern opera book. The book was verified by three academic institution specialists, and the researcher created study instruments such as the verified form and structured interview form. Guangzhou Modern Opera is a significant aspect of Chinese opera, influenced by Western music and reflecting the social status quo. It features vocal music styles such as arias, duets, and choruses, enriching national operas and creating various singing styles. Opera training helps students master stage scheduling and collaborator relationships, fostering cooperation between soloists and orchestras. Technology can serve singing, and singing improves art. The selection of opera not only promotes comprehensive stage practice but also helps students learn opera vocal skills in professional classes, enhancing their performance on stage. Performance books are crucial in teaching vocal music in Guangzhou, representing artistic works in a literary context. The Guangzhou Modern Opera Performance Book is a comprehensive guide for vocalists, covering various aspects of the art form, including theoretical information and singing exercises. The book is based on years of teaching experience and provides a clear understanding of works that can help students advance and make significant strides. The Guangzhou Contemporary Opera Performance Book was evaluated by three experts, who awarded full points for its professional material layout and general quality.